A Case Study of Cluttering Treatment Outcomes in a Teen. (30th June 2015) - Healey, Kearston T.; Nelson, Sarah; Scott, Kathleen Scaler
Abstract: Cluttering is a type of fluency disorder characterized by perceived rapid and/or irregular speech rate and at least one of the following symptoms: excessive disfluencies, the majority of which are non-stuttering-like disfluencies; atypical placement of pausing in speech; and/or excessive over-coarticulation of sounds (St. Louis & Schulte, 2011). Various treatments have been implemented to decrease the rate and increase the clarity of speech in persons who clutter (PWC). This study compared the efficacy of two types of cluttering treatments, pausing and overemphasis, to determine which would reduce the occurrence of over-coarticulation in conversational speech of a teenage male. A decrease in over-coarticulation was exhibited with use of both strategies; however, pausing was determined to reduce the percentage of over-coarticulated words in conversational speech more than overemphasis. This strategy was also the strategy most likely to be implemented in carryover by the participant.